RARE-07. HOW TO TREAT THE INCIDENTAL THALAMIC PRESUMED LOW-GRADE GLIOMAS - Kumabe, Toshihiro (Neuro Oncol, 2019)
Medical intervention for patients with incidentally found presumed low grade gliomas (iLGGs) is controversial. We experienced 5 consecutive thalamic iLGGs, and discuss the follow-up methods and the timing of the intervention. Age at the initial MRI was 19, 57, 58, 70, 70, respectively. Only the bilateral thalamic iLGG of 19-year-old male was radically resected soon after the initial MRI, because of the large tumor size. The histological diagnosis was a diffuse astrocytoma, IDH-wildtype, without H3K27M mutation. This patient was treated by chemoradiation, still alive for 24 months with KPS of 90%. The other four cases were strictly followed by MRI. One case of 70-year-old female is followed for 38 months without increasing the tumor volume. The other 3 cases had been followed by MRI for 15, 91, 154 months, respectively. Stereotactic biopsy or ventriculo-peritoneal shunting (VPS) was performed after that because of the tumor progression. The histological diagnosis of 57-year-old male followed for 15 months was a diffuse astrocytoma, IDH-wildtype. This patient selected further follow-up, although volume of the tumor increased exponentially. Radical resection was performed 11 months after the stereotactic biopsy, disclosed malignant transformation. This patient was treated by chemoradiation, finally died of tumor dissemination 15 months after the radical resection. Long-term followed patients, such as 91 and 154 months, showed slow linear tumor volume increasing. The latter patient with bilateral iLGG was treated by VPS followed by radiation therapy. This patient could keep KPS of 100% for 13 years after the initial MRI and live for 20 years. Our case series suggests that conservative management and close follow-up of thalamic iLGGs is a safe and effective strategy. However, volumetric analysis must be performed for every follow-up MRI. Once the steep volume increasing is detected, surgical intervention and/or chemoradiation should be considered without delay.